Nanoembryonic thermoelastic equilibrium and enhanced properties of defected pretransitional materials. (December 2018) - Xu, Ye-Chuan; Rao, Wei-Feng; Morris, John; Khachaturyan, Armen
Behaviors of displacive phase-transforming materials above the temperature of transformation, where abnormal thermal, elastic, magnetic properties are often observed, are mostly explained by intrinsic peculiarities in electronic/atomic structure. Here, we show these properties may also be attributed to extrinsic effects caused by a thermoelastic equilibrium in highly defected pretransitional materials. We demonstrate that the stress concentration near stress-generating defects such as dislocations and coherent precipitates could result in the stress-induced transformation within nanoscale regions, producing equilibrium embryos of the product phase. These nanoembryos in thermoelastic equilibrium could anhysteretically change their equilibrium size in response to changes in applied stress or magnetic fields leading to superelasticity or supermagnetostriction. Similar response to cooling may explain the observed diffuse phase transformation, changes in the coefficient of thermal expansion and effective elastic modulus, which, in turn, may explain the invar and elinvar behaviors. Displacive transformations: nano-embryos enhance properties Defects that generate stress in a metallic atomic lattice can lead to phase transformations in nanoscale regions under external stimuli. Research led by Wei-Feng Rao at Nanjing University of Information Science and Technology in China used phase field microelasticity simulations to examine local stress around defects (such as dislocations and nanoprecipitates) in materials that undergo displacive martensitic transformations at a certain temperature. They found that stress fields around defects promoted the formation of stable nano-embryos of the product phase even above the transformation temperature. The size of the nano-embryos only depended on the strained lattice and not on temperature, enhancing their sensitivity to external changes in applied stress or magnetic field. The behavior of these nano-embryos can help better understand the superelastic effect in gum metals, supermagnetostriction in iron-based shape memory alloys, and the invar and elinvar effects.